Uncertainties in the Assessment of Individual and Compound Flooding from River Discharge and Coastal Water Levels under Climate Change - Wang, Shuyi (Scholarship@Western, 2020)
It is widely recognized that climate change can impact the risks of flooding in many regions around the world especially the low-lying coastal areas. The concurrent occurrence of multiple flood drivers such as high river flows and coastal water levels can aggravate such impacts causing catastrophic damages. In this study, the individual and compounding effects of riverine and coastal flooding are investigated over Stephenville Crossing, a town located in the coastal-estuarine region of Newfoundland and Labrador (NL), Canada. The impacts of climate change on flood characteristics and the corresponding uncertainties associated with model inputs and structure, and emission scenarios are assessed. A hydrologic model (HEC-HMS) and a 2D hydrodynamic model (HEC-RAS 2D) are setup and calibrated to simulate the flood inundation for the historical period (1976-2005) as well as near future (2041-2070) and far future (2071-2100) periods under Representative Concentration Pathways (RCPs) 4.5 and 8.5. Results of the HEC-RAS 2D model, including the water surface elevations, are then compared with the 1D model simulations. Future storm events are generated based on projected Intensity-Duration-Frequency (IDF) curves from the convection-permitting Weather Research and Forecasting (WRF) climate model simulations, using SCS, Huff, and alternative block design storm methods. The results are compared with simulations based on projected IDF curves that are derived from statistically downscaled General Circulation Models (GCMs) and the uncertainties from different sources are quantified. Overall, the compounding effects of river overflows, sea-level rise, storm surge and wave can result in extensive inundation of the study area under climate change. The uncertainties associated with climate change impact analyses are propagated from GCMs to flood inundation estimations through design storms, projected IDF curves and modeling processes. Simulations based on projected WRF-IDF curves show higher risks of flooding compared to the ones ...